Response of Biology Education Students About Solving Problems of Environmental Pollution at Uin Sunan Kalijaga Yogyakarta - Oktavia, Lusi (Jurnal Pendidikan Biologi Undiksha, 2023)
The problem that we often face in the surrounding environment is in the form of garbage that is everywhere. The waste problem itself occurs not only among households but also often occurs on campuses. As we know, there are many ways that we can use to manage waste, for example, waste can be processed into environmentally friendly products or compost. This study aims to determine the responses of biology education students regarding the resolution of environmental pollution problems at UIN Sunan Kalijaga. This study used a descriptive qualitative research method, with the research instrument using data in the form of a questionnaire, and the respondents were all active semester IV students of FITK biology education.